Accumulation of Carboxylate and Aromatic Fluorophores by a Pest-Resistant Sweet Sorghum [Sorghum bicolor (L.) Moench] Genotype - Uchimiya, Minori (ACS Omega, 2019)
[Image: see text] The sugary juice from sweet sorghum [Sorghum bicolor (L.) Moench] stalks can be used to produce edible syrup, biofuels, or bio-based chemical feedstock. The current cultivars are highly susceptible to damage from sugarcane aphids [Melanaphis sacchari (Zehntner)], but development of new cultivars is hindered by a lack of rapid analytical methods to screen for juice quality traits. The mechanism of aphid resistance/tolerance is also largely unknown, though the importance of defense phytochemicals has been suggested. The purpose of this study was to develop low-cost methods sensitive to fluorescent fingerprints in sweet sorghum juice, which is a complex mixture of saccharides, carboxylates, polyphenols, and metal ions. Of primary juice components, tryptophan and trans-aconitic acid were the highest intensity contributors to the overall fluorescence and UV/visible absorbance, respectively, while tyrosine and polyphenols contributed to a less extent. In a test of 24 sweet sorghum cultivars, tryptophan and tyrosine contents were the highest in the aphid-susceptible hybrid N109A x Chinese, while sucrose, trans-aconitic acid, and polyphenols were the highest in the resistant line No. 5 Gambela. This suggests that the accumulation of carboxylate (trans-aconitic acid) and polyphenolic secondary products in No. 5 Gambela may contribute to its aphid resistance, thus allowing it to maintain sucrose production. Rapid detection of these chemical signatures could be used to prescreen the breeding material for potential resistance and juice quality traits, without analytical separation required for metabolomics.